2023
DOI: 10.1021/acs.est.3c04176
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Photochemical Fate of Methionine in the Presence of Surrogate and Standard Dissolved Organic Matter under Sunlight Irradiation

Benjamin Mohrhardt,
Benjamin Barrios,
Ryan Kibler
et al.

Abstract: The abiotic fate of dissolved free amino acids considerably contributes to the cycling of dissolved sulfur and nitrogen in natural aquatic environments. However, the roles of the functional groups of chromophoric dissolved organic matter (CDOM) and the fate of free amino acids under sunlight irradiation in fresh waters are not fully understood. This study aims to elucidate the fate of photolabile methionine in the presence of three CDOM surrogate compounds, i.e., 1,4-naphthoquinone, 2-naphthaldehyde, and umbel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Figure C suggests that the photomineralization of umbelliferone is oxygen-dependent, while flavone is oxygen independent. Umbelliferone is likely undergoing direct photolysis mediated by oxygen as an electron acceptor, as suggested by other studies, or perhaps is undergoing sensitized reactions with 1 O 2 or another ROS (e.g., O 2 •– ). Conversely, flavone is being degraded through an oxygen independent pathway such as the formation and reaction with a triplet.…”
Section: Resultsmentioning
confidence: 74%
“…Figure C suggests that the photomineralization of umbelliferone is oxygen-dependent, while flavone is oxygen independent. Umbelliferone is likely undergoing direct photolysis mediated by oxygen as an electron acceptor, as suggested by other studies, or perhaps is undergoing sensitized reactions with 1 O 2 or another ROS (e.g., O 2 •– ). Conversely, flavone is being degraded through an oxygen independent pathway such as the formation and reaction with a triplet.…”
Section: Resultsmentioning
confidence: 74%
“…The simulated time-dependent concentration profiles of each species were compared with the experimental results. Here, our previous studies demonstrated two examples of elementary reaction-based kinetic models, as follows: (1) acetone induced by HO • in a UV/H 2 O 2 AOP and (2) methionine induced by PPRIs in the presence of two surrogate CDOMs (i.e., 1,4-naphthoquinone and 2-napthaldehyde) in sunlit fresh waters …”
Section: Time-dependent Concentrations Of a Target Organic Compound A...mentioning
confidence: 95%
“… Elucidation of the photochemical fate of methionine in the presence of surrogate and standard dissolved organic matter under sunlight irradiationMohrhardtB.BarriosB.KiblerR.KingW.DoskeyP. V.MinakataD. Mohrhardt, B. Barrios, B. Kibler, R. King, W. Doskey, P. V. Minakata, D. 10.1021/acs.est.3c04176Environmental Science & Technology2023571436314372 An elementary reaction-based kinetic model based on experimental measurements and quantum chemical computations of the photochemical fate of methionine in the presence of surrogate dissolved organic matter was developed and validated. …”
Section: Key Referencesmentioning
confidence: 99%
See 1 more Smart Citation